Effect of anticoagulant treatment on pain in distal deep vein thrombosis: an ancillary analysis from the cactus trial. (3rd February 2019) - Righini, Marc; Robert‐Ebadi, Helia; Glauser, Frédéric; Blondon, Marc; Ouvry, Pierre; Diamand, Jean‐Marc; Tissot, Anne; Frappe, Paul; Quere, Isabelle; Kahn, Susan R.; Galanaud, Jean‐Philippe; Le Gal, Grégoire
Abstract : Essentials Management of patients with calf deep vein thrombosis remains controversial. We conducted a post‐hoc analysis of a placebo controlled LMWH randomized clinical trial. Pain was assessed using visual analogue scale at inclusion, one and six weeks. There was no difference in pain control between the two arms. Summary: Background: The optimal management of distal deep vein thrombosis (DVT) is highly debated. The only available placebo‐controlled trial suggested the absence of clear benefit of anticoagulation. Many physicians feel that, beyond preventing thromboembolic complications, anticoagulation with low‐molecular‐weight heparin (LMWH) has the potential to improve pain control. Objectives: To analyze whether LMWHs decrease pain in patients with distal deep vein thrombosis. Patients and methods: Two‐hundred and fifty‐two patients included in a multicenter, placebo‐controlled, randomized clinical trial of LMWH in patients with acute distal DVT and who were asked to rate their pain at inclusion and at each medical visit, using a visual analogue pain scale (VAS). Results: One hundred and thirty patients were randomized in the therapeutic nadroparin arm and 122 patients were randomized in the placebo arm. Mean VAS values were 4.6 (standard deviation [SD] 2.5) at inclusion, 2.1 (SD 2.0) at 1 week and 0.4 (SD 1.2) at 6 weeks. We calculated the individual variation in VAS between inclusion and 1 week in patients in whom VAS was available at the two study time‐points. There was no difference in the mean VAS reduction between patients treated with therapeutic nadroparin ( n = 106) and with placebo ( n = 109): −2.6 (SD 2.4) vs. −2.3 (SD 2.0) after 1 week and −4.4 (SD 2.8) vs. −4.0 (SD 2.4) after 6 weeks, respectively. The use of compression stockings was associated with a reduction in pain. Conclusion: These data suggests that LMWH use does not improve pain control as compared with placebo in patients with acute distal DVT.